Effectiveness of varenicline versus nicotine replacement therapy on long-term smoking cessation in primary care: a prospective, cohort study of electronic medical records. (November 2016) - Taylor, Gemma M J; Taylor, Amy E; Thomas, Kyla H; Jones, Tim; Martin, Richard M; Munafò, Marcus R; Windmeijer, Frank; Davies, Neil M
Abstract: Background: No studies have investigated the effectiveness of varenicline versus nicotine replacement therapy (NRT) on long-term (>24 months) smoking cessation in primary care, or whether its effectiveness is altered by socioeconomic status. We aimed to estimate the long-term effectiveness of varenicline on smoking cessation, and to determine whether the effectiveness of varenicline differs by socioeconomic status. Methods: We conducted a prospective cohort study of electronic medical records within the Clinical Practice Research Datalink (CPRD), using three different analytical methods: multivariable logistic regression, propensity score matching, and instrumental variable analyses. Our sample comprised 220 136 patients who were prescribed either NRT (n=149 526) or varenicline (70 610) between Sept 1, 2006, and Sept 30, 2015, who attended 654 general practices in the UK. Primary outcome was smoking cessation at 2 year follow-up. The outcome and covariates were defined with validatedcode lists and algorithms. Socioeconomic status was defined with the Index of Multiple Deprivation (IMD). We used multiple imputation to impute missing values of body-mass index (13·6%) and IMD (0·1%). Findings: Patients prescribed varenicline were more likely than those prescribed NRT to successfully quit smoking after 2 years (odds ratio 1·26, 95% CI 1·23 to 1·29; p<0·0001); results from the propensity score matching were similar. The association persisted up to 4 years' follow-up. Instrumental variable analysis indicated that, for every 100 patients treated with varenicline rather than NRT, an additional 4·99 patients (95% CI 3·01 to 6·98, p<0·0001) would be expected to quit up to 2 years after treatment. On average patients had 2·6 smoking cessation prescriptions in the 2 years after first prescription. We found little evidence that the effectiveness of varenicline differed by socioeconomic status. Interpretation: Patients prescribed varenicline in primary care were less likely to smoke after 2 years than were those prescribed NRT. This is the largest study to date, to our knowledge, to investigate the effectiveness of varenicline for smoking cessation when used in real-world primary care. Although our results could be subject to residual confounding, they are consistent with results from a network meta-analysis and large randomised controlled trial, and together could be used to update clinical guidelines on the use of varenicline for smoking cessation. Funding: This research was funded by the Medical Research Council (MRC) (MR/N01006X/1) and the National Institute for Health Research (NIHR) Health Technology Assessment (HTA) programme (project number 14/49/94). KHT is funded by a clinical lectureship award from the NIHR. RMM is supported by Cancer Research UK (programme grant C18281/A19169) (the Integrative Cancer Epidemiology Programme). TJ is supported by the NIHR CLAHRC West, University Hospitals Bristol NHS Foundation Trust. No funding body has influenced data collection, analysis, or interpretation.